2019
DOI: 10.1111/os.12521
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Prognosis Factors and Predicting the Survival Probability in Patients with Non‐Metastatic Chondrosarcoma from the SEER Database

Abstract: ObjectiveTo identify prognostic factors and establish nomograms for predicting overall survival (OS) and cause specific survival (CSS) of patients with non‐metastatic chondrosarcoma.MethodsWe collected information on patients with non‐metastatic chondrosarcoma from the Surveillance, Epidemiology, and End Results (SEER) database between 2005 and 2014, together with data from the First Affiliated Hospital of Zhengzhou University from 2011 to 2016. Variables including patients’ baseline demographics (age, race, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
(61 reference statements)
5
20
0
Order By: Relevance
“…The result of our study suggested that the risk of death in TCLM patients with Anaplastic was signi cantly higher than that in patients with other histologic type. The studies of Hu P et al [18] and Huang R et al [19] both indicated that grade was an independent predictor of malignancy, and likewise in our study. Previous studies [20] have reported an association between tumor size level and tumor survival.…”
Section: Discussionsupporting
confidence: 90%
“…The result of our study suggested that the risk of death in TCLM patients with Anaplastic was signi cantly higher than that in patients with other histologic type. The studies of Hu P et al [18] and Huang R et al [19] both indicated that grade was an independent predictor of malignancy, and likewise in our study. Previous studies [20] have reported an association between tumor size level and tumor survival.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other malignancies, the grade was also an independent predictor for TCBM. [ 36 , 37 ] The result of our study suggested that the risk of death in TCBM patients with high-level grade (III, IV) was significantly higher than that in patients with low-level grade (I, II). High grade tumors also showed more extensive tumor invasion and the more complications impairing the treatment efficacy.…”
Section: Discussionmentioning
confidence: 70%
“…In this respect, our results are similar to the literature. [11,18] When the relationship between surgical margin conditions and tumor grade is examined, the surgical margin of most Grade 1 cases was R0 and it was usually distributed as R1 and R2 in Stage 2-3 cases. Therefore, although the survival rate of the R0 group was higher than the others, no statistically significant difference was found (p=0.08).…”
Section: Discussionmentioning
confidence: 99%